การพัฒนาโปรแกรมคอมพิวเตอร์ฝึกการเคลื่อนไหวตาแบบสมูทเพอร์สูทร่วมกับเสียงกำกับจังหวะสำหรับวัยรุ่นบาดเจ็บสมองในระดับปานกลาง - ทองสุข, พิทักษ์; เทพสถิตย์ภรณ์, ศราวิน; แก้วแก่น, ปรัชญา (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2022)
การวิจัยนี้มีวัตถุประสงค์เพื่อ 1) พัฒนาโปรแกรมคอมพิวเตอร์ฝึกการเคลื่อนไหวตาแบบสมูทเพอร์สูทร่วมกับเสียงกำกับจังหวะของวัยรุ่นที่ได้รับบาดเจ็บสมองในระดับปานกลาง และ 2) ทดสอบผลของการนำโปรแกรมไปใช้ เป็นการวิจัยเชิงทดลองแบบสองกลุ่ม วัดก่อนและหลังการทดลอง (Pre test-Post test Control Group Design) กลุ่มตัวอย่างเป็นผู้บาดเจ็บสมองในระดับปานกลาง จำนวน 44 คน ได้รับการคัดเลือกตามเกณฑ์ที่กำหนด แบ่งเป็น 2 กลุ่ม คัดเลือกเข้ากลุ่มโดยวิธีการสุ่มอย่างง่าย กลุ่มควบคุม 22 คน ได้รับการดูแลตามปกติ และกลุ่มทดลอง 22 คน ได้รับการฝึกตามโปรแกรมที่พัฒนาขึ้น การศึกษาประกอบด้วย 2 ระยะ ระยะแรก การพัฒนาโปรแกรม โดยการประยุกต์แนวคิดทฤษฎี Biased competition theory of selective attention ของ Desimone and Duncan ทฤษฎี Feature-integration theory of attention ของ Treisman and Gelade และทฤษฎี Premotor theory of attention ระยะที่สอง เป็นระยะทดสอบผลของการนำโปรแกรมไปใช้ เครื่องมือที่ใช้ในการวิจัย ประกอบด้วย เครื่องมือที่ใช้คัดกรองผู้เข้าร่วมวิจัย เครื่องมือที่ใช้ในการทดลอง เป็นโปรแกรมคอมพิวเตอร์ฝึกการเคลื่อนไหวตาแบบสมูทเพอร์สูทร่วมกับเสียงกำกับจังหวะและเครื่องมือที่ใช้วัด ตัวแปรตาม คือ กิจกรรมทดสอบการเรียกคืนความจำแบบการระลึกคำโดยมีตัวชี้แนะ และแบบประเมิน ความพึงพอใจต่อการใช้โปรแกรมฯ วิเคราะห์ข้อมูลด้วยวิธีหาค่าความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และสถิติทดสอบที (t-test) ผลการศึกษาที่สำคัญ 1) โปรแกรมที่พัฒนาขึ้นประกอบด้วย กิจกรรมการฝึก การเคลื่อนไหวตาแบบสมูทเพอร์สูทร่วมกับเสียงกำกับจังหวะ 4 ชุด แต่ละชุดความเร็ว 40, 60, 80 และ 100 ครั้งต่อนาที มีค่าความตรงเชิงเนื้อหา (CVI) อยู่ระหว่าง .91 ถึง 1.00 ใช้เวลาในการฝึกครั้งละ 14 นาที จำนวน 16 ครั้ง 2) หลังการฝึกโปรแกรมคอมพิวเตอร์การเคลื่อนไหวตาแบบสมูทเพอร์สูทร่วมกับเสียงกำกับจังหวะ กลุ่มทดลองมีคะแนนความถูกต้องของการเรียกคืนความจำแบบการระลึกคำโดยมีตัวชี้แนะมากกว่าก่อนการฝึกโปรแกรมคอมพิวเตอร์การเคลื่อนไหวตาแบบสมูทเพอร์สูทร่วมกับเสียงกำกับจังหวะและเพิ่มขึ้นมากกว่ากลุ่มควบคุมอย่างมีนัยสำคัญทางสถิติที่ระดับ .001 สรุป การฝึกโปรแกรมคอมพิวเตอร์การเคลื่อนไหวตาแบบสมูทเพอร์สูทร่วมกับเสียงกำกับจังหวะ อย่างต่อเนื่องช่วยเพิ่มการเรียกคืนความจำแบบการระลึกคำโดยมีตัวชี้แนะของวัยรุ่นที่ได้รับบาดเจ็บสมองในระดับปานกลางได้ คำสำคัญ: การเคลื่อนไหวตาสมูทเพอร์สูท บาดเจ็บสมอง Objectives of research; 1) To develop smooth pursuit eye movement (SPEM) with auditory rhythmic cueing computer program of adolescence in moderate post-traumatic brain injury. 2) To examine the effects of the program. The quasi-experimental research using pretest - posttest control group design was used to examine the program. The subject were 44 people with moderate traumatic brain injury and selected according to the specified criteria. The subject divided into experimental and control group with 22 subjects in each group by simple random method. The control group received normal care and the experimental group were trained according to the developed program. This studying comprised of 2 phases: In the first phase, program was developed by applying Biased competition theory of selective attention by Desimone and Duncan, Feature-Integration theory of attention by Treisman and Gelade and premotor theory of attention. The second phase program was testing the implementation of the program. The instrument consists of screening research subject, The smooth pursuit eye movement (SPEM) with auditory rhythmic cueing computer program, The instruments used to measure dependent variables were the cued recall memory task and the program satisfaction assessment form. Data were analyzed by frequency, percentage, mean, standard deviation, and t-test. Major findings were as follows: 1) The developed program included four sessions. The SPEM level is directed at 40, 60, 80, and 100 times per minute during each session. The CVI (content validity index) ranged from .91 to 1.00. The program consisted of four 14-minute sessions number of 16 times. 2) After training with this program, the experimental group's accuracy of cued recall memory was significantly (p.001) higher than before training programs, and increased more than the control group. Conclusion: The smooth pursuit eye movement with auditory rhythmic cueing computer program of adolescence in moderate post-traumatic brain injury can improve cued recall memory in moderate post-traumatic brain injury patients and they are most effective when used on a daily basis. Keywords: Smooth Pursuit Eye Movement, Traumatic Brain Injury